A new exotic fish for the Mediterranean Sea: Chaetodon auriga Forsskål, 1775 (Perciformes: Chaetodontidae) - TIRALONGO, FRANCESCO; LIPARI, ROBERTO; MANCINI, EMANUELE (Mediterranean Marine Science, 2018)
The presence of Chaetodon auriga Forsskål, 1775 is reported for the first time from the Mediterranean Sea. A specimen was spearfished in 2015 in the central Mediterranean Sea and was in all likelihood an aquarium release. This and similar cases are discussed, with particular emphasis on exotic fishes notoriously known to be commonly kept in aquarium.